Consequences of covid-19 in higher education. Online or presential teaching? - Medina López, Ana; Delgado Jalón, María Luisa; Cámara Sánchez, Ángeles (Journal of Management and Business Education, 2021)
The coronavirus crisis has led to a succession of urgent changes in the field of university education. At Universidad Rey Juan Carlos (URJC), during the first half of 2020, teaching was adapted to the online modality, learning methodologies were transformed and online evaluation was implemented. The university already had a digital platform, although the change had to deal with certain obstacles as some professors and/or students lacked the adequate technological means or did not have the necessary digital skills to abruptly adapt to the new context. When facing next academic year planning, the 2020-21, in the specific case of the Faculty of Legal and Social Sciences (FCJS), which hosts 57% of the total number of students at the URJC, it was necessary to draw the new scenario in which it was decided to return to the classrooms according to a hybrid system. Teachers and students have noted the importance of classroom teaching due to advantages such as the richness of the study environment and university life with all its implications. Given the diversity of the degrees taught at the FCJS, we conclude that online teaching enables interaction between teacher and student but limits the development of certain skills of students in key aspects of this formative stage.